Persistent Piracy
X, 215 p.
Keywords: Spanning from the Caribbean to East Asia and covering almost 3,000 years of history, from Classical Antiquity to the eve of the twenty-first century, Persistent Piracy is an important contribution to the history of the state formation as well as the history of violence at sea.